Beyond the Classics: Reform and Renewal in the Study of Crime and Inequality - Hagan, John (Journal of research in crime and delinquency, 1993)
In this article, the author sketches what he thinks is important about the reformed and renewed focus on inequality and crime and its implications for crime research. The author suggests first that the focus on crime and inequality joins many if not most criminologists in opposition to a largely unspoken but still influential economic and political perspective on crime; second, that an effect of this is to diminish an internal differentiation among criminologists about mechanisms linking crime and inequality; third, that there is a new opportunity for theoretical synthesis reflected in much recent work; and fourth, that these developments have important implications for the future of criminological research. The reformed and renewed interest of criminologists in the influence of inequality provides an important alternative to an economically grounded political philosophy that emphasizes presumed links between inequality, individualism, and efficiency. The latter perspective holds that social inequality enhances individual initiative and is necessary for economic efficiency. It is assumed that social inequality acts as a motivating force that rewards individuals for life choices that lead to efficient and therefore successful economic outcomes. Conversely, social equality is assumed to dampen individual initiative and to produce inefficient, unsuccessful economic results. This suspicion of social equality plays a central role in justifying policies that divert strategic investment from declining communities and disadvantaged individuals